KETELADANAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH - ., Rusihan . (Jurnal Pembelajaran Prospektif, 2019)
This research will explain what teacher competence is and how efforts to improve teacher competency are seen from the role of the principal. Hopefully this article can be used as material for reflection for teachers and other parties with an interest in education. The principal's leadership task will succeed well if a principal understands the task to be carried out. Therefore the principal will appear in a process where he is able to direct, guide, influence and or master the thoughts, feelings or behavior of others. For success in achieving school goals requires professional headmaster's leadership, in which he understands his duties and obligations as a leader, as well as carrying out his role as a leader. In addition,the principal must establish a good cooperative relationship withsubordinates, so as to create a work atmosphere that makes subordinates feel safe, secure, and have a freedom in developing their ideas in order to achieve common goals that have been set.